1958
DOI: 10.1212/wnl.8.3.215
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral changes following discrete lesions of temporal lobe structures

Abstract: o-Toluidine, 6% (v/v) in glacial acetic acid, is used to determine glucose in biologic material after deproteinization with 3% (w/v) trichloracetic acid. A stable green color develops after heating at 1000 for 10 mm., and the absorbance is determined at 630 or 635 mp. The reagent is stable for many months at room temperature, and the reaction follows Beer's Law over a very wide range of concentrations. The development of the procedure is discussed, as is the specificity of the method for glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

1960
1960
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(47 citation statements)
references
References 0 publications
3
42
0
2
Order By: Relevance
“…On the other hand, ablation or stimulation of the lateral part of the amygdala alters sexual behavior (36)(37)(38). Kliiver and Bucy (39), Schreiner and Kling (40) and Green etal.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ablation or stimulation of the lateral part of the amygdala alters sexual behavior (36)(37)(38). Kliiver and Bucy (39), Schreiner and Kling (40) and Green etal.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the central nucleus of the amygdala of the dog results in fear and escape responses (Fonberg, 1965). The same is true for the cat (Anand & Dua, 1956;Wood, 1958). Lesions in the same area, however, result in a reduced threshold for irritable aggression in both animals.…”
Section: Decreased Sensitivity From Neural Inhibitionmentioning
confidence: 55%
“…It also seems likely that a portion of the amygdaloid area which, when stimulated, induces escape behavior, also has inhibitory functions in relation to those areas of the amygdala associated with irritable and predatory aggression (Fonberg, 1965;Wood, 1958). Stimulation of the central nucleus of the amygdala of the dog results in fear and escape responses (Fonberg, 1965).…”
Section: Decreased Sensitivity From Neural Inhibitionmentioning
confidence: 99%
“…Bard and Mountcastle (1948) and Wood (1958) reported that ablation of the amygdala in cat produced an increase in aggression. Elements of the Kluver and Bucy (1939) also hint at contradictory patterns of behavior: amygdalotomy in monkeys produces general placidity, yet hyperactivity, hypersexualty, and hyperreactivity to environmental stimuli.…”
Section: Instrumental Aggression Networkmentioning
confidence: 99%